Of Raids and Returns: Sex work movement, police oppression, and the politics of the ordinary in Sonagachi, India - Dasgupta, Simanti (Anti-Trafficking Review, 2019)
Drawing on ethnographic work with Durbar Mahila Samanwaya Committee (DMSC), a grassroots sex worker organisation in Sonagachi, the iconic red-light district in Kolkata, India, this paper explores the politics of the detritus generated by raids as a form of state violence. While the current literature mainly focuses on its institutional ramifications, this article explores the significance of the raid in its immediate relation to the brothel as a home and a space to collectivise for labour rights. Drawing on atyachar (oppression), the Bengali word sex workers use to depict the violence of raids, I argue that they experience the raid not as a spectacle, but as an ordinary form of violence in contrast to their extraordinary experience of return to rebuild their lives. Return signals both a reclamation of the detritus as well as subversion of the state’s attempt to undermine DMSC’s labour movement.